(untitled) (Международный научный журнал «Инженер», 2026)
In the article, the prediction model of the change in the volume of electricity production in the Republic of Uzbekistan was studied. At the present time, it is important to change the volume of electricity production in the Republic of Uzbekistan. First of all, an econometric analysis of the changes in the volume of electricity production in the period 2010-2022 was carried out. The analysis was carried out on the basis of the MINITAB package. In the analysis, the main statistical indicators were calculated based on the data. A graph is constructed, and periods of changes in the volume of electricity production are studied based on the graph. Based on the statistical data, several trend models were built and a prediction model was selected based on the residuals. Based on the selected model equation, the change in the volume of electricity production for the next 3 years was predicted.